2022
DOI: 10.1038/s41598-022-16097-3
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of immunity and impact of third dose of inactivated COVID-19 vaccine against emerging variants

Abstract: This is a comprehensive report on immunogenicity of COVAXIN® booster dose against ancestral and Variants of Concern (VOCs) up to 12 months. It is well known that neutralizing antibodies induced by COVID-19 vaccines wane within 6 months of vaccination leading to questions on the effectiveness of two-dose vaccination against breakthrough infections. Therefore, we assessed the persistence of immunogenicity up to 6 months after a two or three-dose with BBV152 and the safety of a booster dose in an ongoing phase 2,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…The characteristics of the included studies are summarized in Table 1 . They were conducted one in each of the following countries: India ( 21 ), Singapore ( 20 ), Malaysia ( 16 ), Israel ( 13 ), UK ( 19 ), Qatar ( 12 ), Brazil ( 18 ), Abu Dhabi ( 17 ), Turkey ( 15 ), and China ( 14 ). The proportion of the female ranged from 7.1 to 78.5% and the median age ranged from 33 to 56 years.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are summarized in Table 1 . They were conducted one in each of the following countries: India ( 21 ), Singapore ( 20 ), Malaysia ( 16 ), Israel ( 13 ), UK ( 19 ), Qatar ( 12 ), Brazil ( 18 ), Abu Dhabi ( 17 ), Turkey ( 15 ), and China ( 14 ). The proportion of the female ranged from 7.1 to 78.5% and the median age ranged from 33 to 56 years.…”
Section: Resultsmentioning
confidence: 99%
“…This study found that prevalence of a booster dose uptake was 50% as of the follow-up survey, which was similar to the figure (46.6%) among people aged 20 or above as of 13 April 2022 reported by the Hong Kong government [ 13 ]. It has been documented that receiving a booster dose contributes to preventing not only infection, but also negative consequences caused by COVID-19 [ 9 , 10 , 11 ]. Thus, promoting uptake of a booster dose in Hong Kong is still a necessity.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the waning immunity and the uncertain efficacy of vaccines against newly rapid emerging variants, uptake of a booster dose is of great importance. It has been documented that uptake of a booster dose of COVID-19 vaccine not only ensures persistent immunity, but also contributes to fighting against newly emerging variants [ 9 ]. Real-world evidence showed that compared to close contacts who received two doses, those who received a booster dose were less likely to be infected [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recent study also demonstrated a similar result in the substantially reduced humoral B-cell levels measured using the CYTOF method in humans after a month of immunizing with the inactivated vaccine [26]. The specific SAR-CoV 2 antibody level was maintained for at least 6 months after vaccination with the inactivated vaccine [27]. The high antibody level after the vaccination highlights the memory immune response and signifies the importance of booster immunization.…”
Section: Discussionmentioning
confidence: 66%